1996
DOI: 10.1002/(sici)1097-0290(19960405)50:1<24::aid-bit4>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial microbial distributions of nitrifiers and heterotrophs in mixed-population biofilms

Abstract: Spatial microbial distributions of nitrifiers and heterotrophs in undefined mixed‐population biofilms were experimentally investigated using a microslicer technique and correlated with nitrification efficiency of the biofilm system. The general stratification of different bacterial groups in the biofilm was simulated using a one‐dimensional (1‐D) mathematical biofilm accumulation model (BAM) and compared with the experimental results. Biofilms were cultured at three C : N ratios of feed solutions in a partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 28 publications
(5 reference statements)
5
55
2
3
Order By: Relevance
“…However, when the ecosystem is supplied with organic carbon, the heterotrophic bacteria compete with the nitrifiers for ammonia and oxygen and are always the winner due to their faster growth rate. As a result, the nitrification efficiency is reduced in most cases [8,11,12].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, when the ecosystem is supplied with organic carbon, the heterotrophic bacteria compete with the nitrifiers for ammonia and oxygen and are always the winner due to their faster growth rate. As a result, the nitrification efficiency is reduced in most cases [8,11,12].…”
Section: Introductionmentioning
confidence: 77%
“…Many studies have reported that the overgrowth of nitrifiers by heterotrophs resulted in a lower nitrifying capacity of the biofilm reactor with the supplement of organics [8,11,12]. However, in our experiment, the nitrite removal rate did not fall as the normal culture was supplied with sodium acetate, although both the total protein and community structure analyses indicated that the heterotrophic bacteria were the majority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SM presence can favor bacteria distribution with faster growth rate in upper biofilm layers (where substrate passage and microorganisms shedding is higher), while slow growing nitrifying bacteria, grow inside the biofilm, preventing their drag out from the reactor, thus, biofilm formed of heterotrophic bacteria may present a greater thickness than biofilms composed of autotrophic bacteria (Okabe et al,1996a). Bassin et al (2012) when analyzing biofilm on micrographs, observed that nitrifying biomass is significantly changed when effluent COD is reduced, it was also noticed that in some parts of its SM, biofilm detachment was registered when COD was diminished.…”
Section: Scanning Electronic Microscopy (Sem)mentioning
confidence: 99%
“…El control de la edad del fango en el reactor biológico, por tanto, es un parámetro importante en la operación de las depuradores. Normalmente los fangos aerobios granulares son más heterogéneos en relación a las bacterias que coexisten en su interior y a las micro-características morfológicas de la biopelícula (De Beer et al 1996) (Okabe et al 1996).…”
Section: Competencia Autótrofas/heterótrofasunclassified